Lactic acid and animal feeds production from Sophora flavescens residues by Rhizopus oryzae fermentation. (May 2020) - Ma, Xiaoyu; Gao, Ming; Yin, Zihe; Zhu, Wenbin; Liu, Sijia; Wang, Qunhui
Graphical abstract: Highlights: Lactic acid and animal feeds could be obtained from Sophora flavescens residues. A total of 46.78 g/L lactic acid was obtained under optimal fermentation conditions. The protein content of residual solid part improved from 0.26 % to 12.15 %. The residual solid residues after fermentation were rich in Fe and Zn. Economic analysis suggested that this method of waste utilization was promising. Abstract: In this study, the feasibility of producing lactic acid and animal feeds from Sophora flavescens residues (SFR) by Rhizopus oryzae was explored. Results showed that the simultaneous saccharification and fermentation (SSF) is the optimal fermentation mode, which was simple and high-efficiency. When the inoculation volume of R. oryzae was 10 % and the pH value was adjusted by adding CaCO3 in stages during SSF, the maximum concentration of lactic acid was 46.78 g/L, and the maximum lactic acid productivity reached 0.97 g/L/h. Results also showed that the protein content of the solid residues after fermentation of R. oryzae reached 12.15 %. This content was 46 times higher than that by the original SFRs and nearly 4.3 times the protein content of the solid residues after fermentation by Enterococcus faecium . In addition, the solid residues after fermentation rich in Fe and Zn could be used as animal feeds or feed additives. Thus, it is expected that this study may provide a novel approach for Chinese medicine residues treatment towards full resource recovery.